ANALISIS KECUKUPAN GURU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR DI KABUPATEN BANTUL - Mukminan Mukminan (Universitas Negeri Yogyakarta, 2010)
This study is aimed at knowing the adequacy of elementary school Islamic education teachers in Bantul regency, in relation with the number of teachers, number of teaching hours, and the distribution by district.A survey of the real condition in the field, the study formulates a map of the religious teachers in the regency.Data of the study are collected by questionnaire and documentation and are analyzed using the quantitative descriptive technique.Research results show: (1) the general condition of the current number of the religious teachers can be considered as sufficient, the number 69 people even has excess; (2) with the assumption of the fixed number of the student groups for the Islamic classes, teacher outside/inside mutations are not likely to occur. Bantul regency projects a surplus of religious teachers to as many as 17 persons until the year 2014